PENINGKATAN HASIL BELAJAR PERKALIAN MENGGUNAKAN MODEL PEMBELAJARAN NUMBERED-HEADS TOGETHER PADA SISWA KELAS III-B MI MASYHUDIYAH GRESIK - Rohmah, Nur Hidayatur (Journal Of Islamic Elementary School (JIES), 2019)
This study aims to determine the application of Numbered-Heads Together learning model and increase the results of mathematics learning multiplication material in class III-B MI Masyhudiyah Gresik. This research is a classroom action research using the Kurt Lewin model. The data of this study were obtained by observation, interviews, written tests, non-tests and documentation. The results of the study show: This research has been going well and has succeeded in experiencing an increase in mathematics learning outcomes through the Numbered-Heads Together (NHT) learning model in Class III-B students at MI Masyhudiyah. This can be seen from the results of the final value of the teacher’s activity in the first cycle that gets 82.5 (good) and increases in the second cycle to 95.83 (very good). Whereas, the final value of student activities also experienced an increase from cycle I by 80 (good) to 95 (very good) on cycles II. This can also be proven by the value of learning outcomes in the pre cycle, cycle I and cycle II. In the pre cycle the percentage of class success was 57.89% (less) and an average of 72.10 (sufficient), cycle I was obtained by the success percentage of class 78.94% (good) and an average of 80.46 (good) and in the cycle II the percentage of class success and average increased by 94.73% (very good) and an average of 91.91 (very good) and had met the specified performance indicators.